Дизајнирање на формата за адитивно производство - Џокиќ, Јелена (Машински факултет, УКИМ, Скопје, 2020)
Additive manufacturing (AM) technologies emerge in the late 90ties and since then, they experienced rapid growth and development. The development of these technologies creates new opportunities for their application in different areas. This raises interest in the industry and so in academic circles. One of the most important advantages of the AM is fabrication of forms with complex geometry. This particular aspect made them very popular among the industrial designers which are being limited from the traditional technologies. AM technologies work in opposite manner that the traditional technologies, and that is by adding material, which creates numerous advantages but also challenges that has to be overcome by the user. The interest of the industrial designers for these technologies creates need for additional research in way of familiarizing AM to them. In order to produce parts with AM they should be CAD models, which mean that the development of the technologies should be followed by the software packages. The software packages for parametric modeling can withstand the need for complex geometry creation. In this doctoral dissertation, tool that will help industrial designers in the process of design for AM is developed. The tool is a collection of rules which should point industrial designers towards for “appropriate” design for AM. In addition, benchmark model is designed, which is intended to guide the user in the process of fabrication but also help in the evaluation and optimization of the machine. In order for them to be more specific, the rules and the benchmark model are developed for one particular process and that is material extrusion (fused filament fabrication - FFF). Material extrusion and open source machines working on that principle are analyzed in this doctoral dissertation because they offer more research opportunities and are widely used among the industrial designers.
Form design for additive manufacturing
Докторска дисертација одбранета во 2020 година на Машинскиот факултет во Скопје, под менторство на проф. д–р Татјана Кандикјан.
Keywords: design for additive manufacturing (DfAM), additive manufacturing technologies, material extrusion, fused filament fabrication (FFF), parametric design, industrial design